Pengembangan Bahan Ajar Berbasis Ecoliteracy Lokal Sumatera Utara pada Materi Puisi di Kelas X Sekolah Menengah Atas Swasta Pertiwi Medan. - Ermiyanti Siringo Ringo; Rita Rita; Rika Kartika (Medan Resource Center, 2026)
This study aims to describe the development, validation, feasibility, and effectiveness of teaching materials based on the local ecoliteracy of North Sumatra for poetry instruction in grade X. The research was conducted at SMA Swasta Pertiwi Medan using a Research and Development (R&D) approach with the 4D model. The population consisted of 44 students from grade X Ibnu Sina and X Ki Hadjar Dewantara, with a sample of 22 students from grade X Ibnu Sina. Both qualitative and quantitative data were employed in the study. The developed product was a textbook that integrates local ecoliteracy into poetry learning. Validation by material experts resulted in a “Very Feasible” rating of 88%, while validation by design experts achieved a “Very Feasible” rating of 93%. Teacher responses indicated 94% feasibility, and student responses yielded 87%, demonstrating strong acceptance of the textbook. Overall, the teaching materials were categorized as “Valid” and “Very Appropriate” with an average percentage of 92%. Furthermore, the effectiveness test conducted through evaluation activities showed that the teaching materials achieved a “Very Effective” category with a score of 87%. These findings confirm that ecoliteracy-based teaching materials are valid, feasible, and effective for enhancing poetry learning in senior high school.